Extremely cold-resistant environment-friendly modified regenerated rubber sole composite material and preparation method thereof

By preparing extremely cold-resistant and environmentally friendly modified regenerated rubber sole composite materials, using modified SBR, modified silicone and environmentally friendly modified regenerated masterbatch, the problem of waste rubber in extremely cold environments is solved, and the material has high cold resistance, fold resistance and environmental protection are achieved.

CN119912734APending Publication Date: 2025-05-02ZHEJIANG LONGXING KAITAI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510090962.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art is difficult to effectively deal with waste rubber, especially in extremely cold environments, and its low temperature fold resistance and mechanical properties cannot meet the practical application requirements.

Method used

Prepare extremely cold-resistant and environmentally friendly modified regenerated rubber sole composite materials, and form composite materials with good cold resistance and self-repairing properties through the combination of modified SBR, modified silicone, environmentally friendly modified regenerated masterbatch and other components.

Benefits of technology

It has achieved excellent low temperature and fold resistance in extremely cold environments below -60℃, and can maintain 40,000 fold resistance without cracks. It also has good anti-slip and wear resistance, effectively recycling waste rubber and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251521970000141
    Figure BDA0005251521970000141
Patent Text Reader

Abstract

The invention discloses an extremely cold-resistant environment-friendly modified regenerated rubber sole composite material and a preparation method thereof, and belongs to the technical field of sole materials. The extremely cold-resistant environment-friendly modified regenerated rubber sole composite material is prepared from the following raw material components in parts by weight: 10 to 15 parts of modified SBR (Styrene Butadiene Rubber), 15 to 20 parts of NR (Natural Rubber), 65 to 75 parts of BR (Butadiene Rubber), 5 to 10 parts of modified silica gel, 2 to 4 parts of phenolic resin and 20 to 30 parts of environment-friendly modified regenerated master batch, the formula comprises the following components in parts by mass: 40-50 parts of white carbon black, 5-8 parts of zinc oxide, 8-12 parts of PEG4000, 0.8-1.2 parts of stearic acid, 4-5 parts of an antioxidant, 1-3.5 parts of sulfur and 1-3.5 parts of an accelerant. The modified SBR is obtained by carrying out copolymerization on styrene, butadiene and 4-vinyl benzyl bromide and then carrying out epoxidation grafting on perfluoropolyether alcohol and 5-amino-1-pentanol to carry out a reaction; the modified silica gel is prepared from methyl vinyl silicone rubber modified by mercaptopropionaldehyde, ethyl mercaptoacetate and 1, 3-dimercaptopropane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an extreme cold resistant and environment-friendly modified recycled rubber sole composite material and a preparation method thereof. Background Art

[0002] Rubber products have greatly improved our quality of life with their excellent wear resistance, corrosion resistance and excellent elasticity. However, while enjoying these conveniences, we are also facing a severe environmental challenge: the problem of waste rubber disposal. During the vulcanization process, rubber forms a very stable C-Sx-C bond and CC bond covalent cross-linking network through sulfur or peroxide, which makes waste rubber difficult to melt and dissolve, and difficult to effectively dispose of. A large amount of improperly treated rubber waste has gradually accumulated, forming the so-called "black pollution", such as waste tires, rubber tubes, rubber shoes and other scraps.

[0003] These waste rubbers that have not been effectively treated will not only seriously pollute the land, water and air, but may also cause safety hazards such as fires. According to relevant statistics, the number of waste tires produced in my country each year is huge and is increasing year by year. How to deal with these waste rubbers efficiently and environmentally friendly has become a major problem that needs to be solved urgently. Although the current rubber recycling technology has made certain progress, there are still problems such as high energy consumption, heavy pollution, and unstable quality of recycled rubber, which makes it difficult to meet the modern industry's demand for environmental protection, high efficiency, and high performance.

[0004] In addition, traditional recycled rubber has poor performance in low-temperature environments, especially in extremely cold areas or extreme weather conditions. Its low-temperature folding resistance and mechanical properties cannot meet the requirements of practical applications.

[0005] Therefore, the applicant prepared an extreme cold resistant and environmentally friendly modified recycled rubber sole composite material. Summary of the invention

[0006] The purpose of the present invention is to provide an extreme cold resistant and environmentally friendly modified recycled rubber sole composite material and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.

[0007] The technical solution for achieving the purpose of the present invention is:

[0008] The first aspect of the present invention provides an extreme cold resistant and environmentally friendly modified recycled rubber sole composite material. The raw material components include, by weight, 10 to 15 parts by weight of modified SBR, 15 to 20 parts by weight of NR, 65 to 75 parts by weight of BR, 5 to 10 parts by weight of modified silica gel, 2 to 4 parts by weight of phenolic resin, 20 to 30 parts by weight of environmentally friendly modified recycled masterbatch, 40 to 50 parts by weight of white carbon black, 8 to 12 parts by weight of PEG4000, 0.8 to 1.2 parts by weight of stearic acid, 4 to 5 parts by weight of antioxidant, 1 to 3.5 parts by weight of sulfur, and 1 to 3.5 parts by weight of accelerator.

[0009] Furthermore, the modified SBR is obtained by copolymerizing styrene, butadiene and 4-vinylbenzyl bromide, and then epoxidizing and grafting perfluoropolyether alcohol and 5-amino-1-pentanol.

[0010] Furthermore, the modified silica gel is obtained by modifying methyl vinyl silicone rubber with mercaptopropionaldehyde, ethyl mercaptoacetate and 1,3-dimercaptopropane.

[0011] Furthermore, the environmentally friendly modified recycled masterbatch is obtained by crushing and cutting the waste rubber soles from which non-rubber impurities are removed into rubber particles, kneading the rubber particles with octadecyl ammonium and aromatic oil, and then mixing and thinning with natural rubber, zinc oxide and a cold-resistant agent.

[0012] The second aspect of the present invention provides a method for preparing an extreme cold resistant and environmentally friendly modified recycled rubber sole composite material, comprising the following preparation steps:

[0013] (1) weighing and preparing the raw material components of the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material according to the first aspect;

[0014] (2) adding the modified SBR and modified silica gel weighed in step (1) to an internal mixer and premixing for 3 to 5 minutes; then adding 4 to 8 parts by weight of carbon disulfide and heating to 75 to 85° C., mixing for 15 to 25 minutes, then cooling to room temperature and adding NR, BR, and phenolic resin, and continuing to mix for 3 to 5 minutes, then heating to 55 to 65° C., adding environmentally friendly modified recycled masterbatch and white carbon black in sequence, and mixing for 13 to 17 minutes; then continuing to add PEG4000, stearic acid, and antioxidant to the internal mixer, mixing for 6 to 10 minutes, and then starting to discharge; then passing through a double-roll plasticizer for 4 times to produce a thin sheet, the roller temperature is controlled at 60° C., the roller gap is adjusted to 0, and the roller gap is adjusted to 0.5 mm when the sheet is discharged, and the sheet is cooled at room temperature and placed for at least 24 hours;

[0015] (3) The thin sheet obtained in step (2) and the sulfur and accelerator weighed in step (1) are introduced into an open mill for 3 to 6 minutes to produce a sheet, and after cooling at room temperature for at least 12 hours, injection molding is performed to obtain an extreme cold resistant and environmentally friendly modified recycled rubber sole.

[0016] Furthermore, the preparation steps of the modified SBR are as follows:

[0017] A1. Under argon protection, 600 parts by mass of cyclohexane, 44 to 46 parts by mass of deoxygenated styrene, 39 to 41 parts by mass of 4-vinylbenzyl bromide and 15 parts by mass of butadiene monomer, 0.4 to 0.6 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 39 to 41 ° C and preheated for 20 min; 580 to 584 parts by mass of 1.6 mol / L n-butyl lithium solution was added dropwise at 1 to 3s / drop, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking was completed to obtain a broken hard segment material;

[0018] A2. Under argon protection, 600 parts by mass of cyclohexane, 9 to 11 parts by mass of styrene treated by deoxygenation, 19 to 21 parts by mass of 4-vinylbenzyl bromide and 70 parts by mass of butadiene monomer, 0.4 to 0.6 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 39 to 41 ° C for 20 minutes; 840 to 844 parts by mass of 1.6 mol / L n-butyl lithium solution was added dropwise at 1 to 3s / drop, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light When it turns yellow, the impurities are broken, and then the polymerization reaction is initiated at 39-41°C for 39-41 minutes to obtain a soft segment, and then the impurities-broken hard segment is added, and the reaction is continued for 19-21 minutes. After the reaction is completed, 400-500 parts by weight of SnCl4 are added to continue the reaction for 19-20 minutes, and 108-112 parts by weight of isopropanol are added to terminate the reaction, and after water vapor condensation, it is extruded on a 120°C open mill to remove water to obtain a pre-modified SBR; the mass ratio of the soft segment to the impurities-broken hard segment is 5-7:3-5;

[0019] A3. 10 to 15 parts by mass of pre-modified SBR and 100 parts by mass of cyclohexane were mixed and stirred at 45 to 55 r / min to mix evenly, and then 19 to 21 parts by mass of formic acid and 1.5 to 2.5 parts by mass of tween80 were added. After mixing evenly, the temperature was raised to 39 to 41°C, and 11 to 13 parts by mass of hydrogen peroxide were added dropwise at a rate of 1 to 3 seconds per drop. After the addition was completed, the reaction was continued for 23 to 25 hours, and then sodium carbonate was added to adjust the pH to neutral, and the oil phase was washed twice with deionized water and condensed with ethanol, and then washed and dried to obtain epoxidized pre-modified SBR;

[0020] A4. 9 to 11 parts by mass of epoxidized pre-modified SBR, 75 to 80 parts by mass of perfluoropolyether alcohol, and 7 to 9 parts by mass of 5-amino-1-pentanol are dissolved in 100 parts by mass of dimethyl sulfoxide, respectively, and then the three are mixed, and 0.01 to 0.03 parts by mass of tetrabutylammonium chloride are added. After stirring and reacting at room temperature for 1.5 to 2.5 hours, the temperature is raised to 54 to 56°C and the reaction is continued for 1.5 to 2.5 hours. After the solution is cooled to room temperature, the gum is precipitated with anhydrous ethanol, washed 3 to 5 times, and dried to obtain modified SBR.

[0021] Further, the preparation method of the modified silica gel is as follows: 10 parts by mass of methyl vinyl silicone rubber is dissolved in 100 parts by mass of THF, and the methyl vinyl silicone rubber is stirred until the methyl vinyl silicone rubber is completely dissolved, and then 1 to 5 parts by mass of a mercapto modifier is added, wherein the mercapto modifier is obtained by mercaptopropionaldehyde, ethyl mercaptoacetate, and 1,3-dimercaptopropane in a mass ratio of 2:0.5 to 1.5:1.5 to 2.5, and the stirring is continued for 25 to 35 minutes, and 0.25 to 0.27 parts by mass of an initiator benzil dimethyl ether is added, and then in a closed cavity Indoors, a UV-LED point light source with a wavelength of 365nm is used for irradiation for 1 to 2 hours. After the reaction is completed, a mixed solution of ethanol and deionized water with a volume ratio of 1:1 is used to precipitate the glue, and then it is dissolved in tetrahydrofuran again and the glue is precipitated with a mixed solution of ethanol and deionized water. This is repeated three times to remove free thiol small molecules and avoid the odor of thiol reagents. Finally, it is placed in a vacuum oven at 40 to 50°C and dried for 23 to 25 hours, and then placed in 14 to 19 parts by mass of 2M potassium hydroxide solution, stirred for 1 to 2 hours and filtered to obtain modified silica gel.

[0022] Furthermore, the preparation method of the environmentally friendly modified recycled masterbatch is as follows:

[0023] B1. Remove non-rubber impurities from the collected waste rubber soles, and then cut and crush them into rubber particles with a particle size of 5 to 15 mm;

[0024] B2. Add rubber particles, octadecyl ammonium and aromatic oil in a mass ratio of 100:2-5:8-13 into a high-speed mixer and mix for 5-7 minutes, wherein the temperature of the high-speed mixer is set at 73-77°C, and cool at room temperature after discharge to obtain environmentally friendly recycled materials;

[0025] B3. Add 20-30 parts by mass of environmentally friendly recycled materials, 4-6 parts by mass of natural rubber, 5-8 parts by mass of zinc oxide, and 15-20 parts by mass of cold-resistant agent into a mixer and mix for 3-5 minutes. When the temperature rises to 100°C, discharge the material to a calender and thin it three times at room temperature to produce a sheet of environmentally friendly modified recycled masterbatch with a thickness of 4-6 mm.

[0026] Furthermore, the cold-resistant agent is obtained by compounding dioctyl sebacate and dioctyl phthalate in a mass ratio of 1:1.2 to 3.5.

[0027] Furthermore, the accelerator is prepared by compounding 2,2'-dibenzothiazole disulfide, tetramethylthiuram monosulfide, N-tert-butyl-2-benzothiazole sulfenamide, and diphenylguanidine in a mass ratio of 12:1:2:2.

[0028] The antioxidant is selected from any one or a combination of antioxidant RD, antioxidant SP, and antioxidant MB.

[0029] By adopting the above technical solution, the present invention has the following beneficial effects:

[0030] (1) The extremely cold resistant and environmentally friendly modified recycled rubber sole composite material of the present invention is prepared from the following raw material components in parts by weight: 10 to 15 parts by weight of modified SBR, 15 to 20 parts by weight of NR, 65 to 75 parts by weight of BR, 5 to 10 parts by weight of modified silica gel, 2 to 4 parts by weight of phenolic resin, 20 to 30 parts by weight of environmentally friendly modified recycled masterbatch, 40 to 50 parts by weight of white carbon black, 8 to 12 parts by weight of PEG4000, 0.8 to 1.2 parts by weight of stearic acid, 4 to 5 parts by weight of antioxidant, 1 to 3.5 parts by weight of sulfur, and 1 to 3.5 parts by weight of accelerator; the obtained extremely cold resistant and environmentally friendly modified recycled rubber sole composite material has good cold resistance and folding resistance.

[0031] (2) The modified SBR of the present invention is prepared by copolymerizing styrene, butadiene and 4-vinylbenzyl bromide through carbon-carbon double bonds, and then epoxidizing the copolymer. Finally, the epoxy group is ring-opened through active groups such as hydroxyl groups in perfluoropolyether alcohol and 5-amino-1-pentanol, and the flexible molecular chains perfluoropolyether alcohol and 5-amino-1-pentanol are grafted onto the side chains of the copolymer. This can increase the activity space of the modified SBR polymer chain and reduce the intermolecular interaction force, and effectively interfere with the crystallinity of the modified SBR, effectively reduce the Tg of the modified SBR, and enhance the cold resistance of the extremely cold resistant and environmentally friendly modified recycled rubber sole composite material; at the same time, the flexible molecular chain can provide additional energy absorption pathways under stress, slow down the propagation speed of cracks, and enhance the folding resistance of the extremely cold resistant and environmentally friendly modified recycled rubber sole composite material.

[0032] (3) The modified silica gel of the present invention is obtained by grafting mercaptopropionaldehyde, ethyl mercaptoacetate and 1,3-dimercaptopropane onto methyl vinyl silicone rubber through a mercapto-ene click reaction. By introducing ester carboxyl groups, aldehyde groups and mercapto groups into methyl vinyl silicone rubber, the regular structure of the modified silica gel can be effectively destroyed, and the low-temperature crystallization of the modified silica gel can be inhibited, thereby further improving the cold resistance of the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material.

[0033] (4) When preparing the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material of the present invention, the modified SBR, modified silica gel, and carbon disulfide are firstly subjected to banburying, and then NR, BR, phenolic resin, environmentally friendly modified recycled masterbatch, and white carbon black are added in sequence for mixing. During the banburying of the modified SBR, modified silica gel, and carbon disulfide, the mercaptide salt on the modified silica gel reacts with carbon disulfide and benzyl bromide in the modified SBR to form a benzyl trithiocarbonate derivative. When the environmentally friendly modified recycled masterbatch is subsequently added and banburying is performed at 55 to 65° C., free radicals are generated in the rubber macromolecular chains of the environmentally friendly modified recycled masterbatch, and the SC activity at the benzyl position in the benzyl trithiocarbonate derivative is activated. The benzyl group will couple and terminate with R·, thereby preventing R· from recombining by stabilizing free radicals, degrading the three-dimensional cross-linked network, reducing the cross-linking density of the environmentally friendly modified recycled masterbatch, and performing secondary regeneration and degradation of the environmentally friendly modified recycled masterbatch, thereby increasing the fluidity and plasticity of the environmentally friendly modified recycled masterbatch, and further enhancing the mechanical properties of the extreme cold resistant environmentally friendly modified recycled rubber sole composite material; at the same time, the amino group on the modified SBR reacts with the aldehyde group of the modified silica gel to form a dynamically reversible imine bond, which increases the cross-linking density of the extreme cold resistant environmentally friendly modified recycled rubber sole composite material and gives the extreme cold resistant environmentally friendly modified recycled rubber sole composite material good self-healing properties.

[0034] (5) The present invention firstly destroys the relatively long network structure of the vulcanized rubber by a physical method of cutting or crushing, and then dissolves the cross-linked structure of the vulcanized rubber by using octadecyl ammonium and aromatic oil activators to generate free radicals. The free radicals can accelerate the thermal oxidation rate or act as free radical acceptors to stabilize the rubber free radicals generated by thermal oxidation and prevent them from recombining. A small amount of activator can show a significant regeneration effect and can greatly shorten the desulfurization time.

[0035] (6) The cold-resistant agent of the present invention is prepared by compounding dioctyl sebacate and dioctyl phthalate in a mass ratio of 1:1.2 to 3.5, wherein dioctyl sebacate and dioctyl phthalate are both low-temperature plasticizers, which can improve the mechanical properties of the rubber, reduce Tg, and increase the maximum elongation at low temperature; they also increase the fluidity and leveling of the mixed rubber; and have no effect on the vulcanization of the rubber, and can also play a certain role as a lubricant.

[0036] (7) The extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material prepared by the present invention has excellent low-temperature resistance and folding resistance, can be maintained in an extremely cold environment below -60°C, and can withstand 40,000 folds without cracks; at the same time, it has good anti-slip and wear-resistant effects; the present invention effectively recycles the waste rubber generated in the production, reduces the black pollution to the environment, and can also alleviate the problem of excessive use and waste of rubber resources. DETAILED DESCRIPTION

[0037] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0038] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.

[0039] Some of the raw materials of the embodiments of the present invention and the comparative examples are as follows:

[0040] NR: purchased from Hengshui Shuangli Rubber Technology Co., Ltd., model STR5;

[0041] BR: Beijing Yanshan Branch of Sinopec, model BR9000;

[0042] Antioxidant selection antioxidant RD:

[0043] The accelerator is prepared by mixing 2,2'-dibenzothiazole disulfide, tetramethylthiuram monosulfide, N-tert-butyl-2-benzothiazole sulfenamide and diphenylguanidine in a mass ratio of 12:1:2:2.

[0044] Perfluoropolyether alcohol: average molecular weight 1000, Fuzhou Taipuda New Materials Co., Ltd.;

[0045] Methyl vinyl silicone rubber: Methyl vinyl silicone rubber with a vinyl chain mole fraction of 10%.

[0046] The cold-resistant agent is prepared by mixing dioctyl sebacate and dioctyl phthalate in a mass ratio of 1:2.4.

[0047] (Example 1)

[0048] The preparation method of the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material comprises the following preparation steps:

[0049] (1) Weigh and prepare the following raw material components in parts by weight: 10 parts by weight of modified SBR, 15 parts by weight of NR, 65 parts by weight of BR, 5 parts by weight of modified silica gel, 2 parts by weight of phenolic resin, 20 parts by weight of environmentally friendly modified recycled masterbatch, 40 parts by weight of white carbon black, 8 parts by weight of PEG4000, 0.8 parts by weight of stearic acid, 4 parts by weight of antioxidant, 1 part by weight of sulfur, and 1 part by weight of accelerator;

[0050] (2) adding the modified SBR and modified silica gel weighed in step (1) to an internal mixer and premixing for 3 minutes; then adding 4 parts by mass of carbon disulfide and heating to 75° C., mixing for 15 minutes, then cooling to room temperature and adding NR, BR, and phenolic resin, and continuing to mix for 3 minutes, then heating to 55° C., adding environmentally friendly modified recycled masterbatch and white carbon black in sequence, and mixing for 13 minutes; then continuing to add PEG4000, stearic acid, and antioxidant to the internal mixer, mixing for 6 minutes and starting to discharge; then passing the mixture through a double-roll plasticizer for 4 times to produce a thin sheet, the roller temperature is controlled at 60° C., the roller distance is adjusted to 0, that is, the roller distance is 0, and the roller distance is adjusted to 0.5 mm when the sheet is discharged, and the mixture is cooled at room temperature and placed for at least 24 hours;

[0051] (3) The thin slices obtained in step (2) and the sulfur and accelerator weighed in step (1) are introduced into an open mill for refining for 3 minutes to produce sheets, and after cooling at room temperature for at least 12 hours, injection molding is performed to obtain an extreme cold resistant and environmentally friendly modified recycled rubber sole.

[0052] Wherein, the preparation steps of modified SBR are as follows:

[0053] A1. Under argon protection, 600 parts by mass of cyclohexane, 44 parts by mass of deoxygenated styrene, 41 parts by mass of 4-vinylbenzyl bromide and 15 parts by mass of butadiene monomer, 0.4 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 39 ° C and preheated for 20 min; 580 parts by mass of 1.6 mol / L n-butyl lithium solution was added dropwise at 1s / drop, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the broken impurities were completed to obtain a broken impurity hard segment material;

[0054] A2. Under argon protection, 600 parts by mass of cyclohexane, 9 parts by mass of deoxygenated styrene, 21 parts by mass of 4-vinylbenzyl bromide and 70 parts by mass of butadiene monomer, 0.4 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 39°C for preheating for 20 minutes; 840 parts by mass of 1.6 mol / L n-butyl lithium solution were added at 1s / drop, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking of impurities was completed, and then the polymerization reaction was initiated at 39°C for 39 minutes to obtain a soft segment material, and then the hard segment material with impurities was added, and the reaction was continued for 19 minutes. After the reaction was completed, 400 parts by mass of SnCl4 was added to continue the reaction for 19 minutes, and 108 parts by mass of isopropanol were added to terminate the reaction, and after water vapor condensation, it was extruded on a 120°C open mill to remove water to obtain a pre-modified SBR; the mass ratio of the soft segment material to the hard segment material with impurities was 5:5;

[0055] A3. 10 parts by mass of pre-modified SBR and 100 parts by mass of cyclohexane were mixed and stirred at 45 r / min to mix evenly, followed by adding 19 parts by mass of formic acid and 1.5 parts by mass of tween80, mixing evenly, heating to 39°C, adding 11 parts by mass of hydrogen peroxide at 1s / drop, reacting for 23h after the addition, then adding sodium carbonate to adjust the pH to neutral, washing twice with deionized water, taking the oil phase and condensing it with ethanol, and then washing and drying to obtain epoxidized pre-modified SBR;

[0056] A4. 9 parts by mass of epoxidized pre-modified SBR, 75 parts by mass of perfluoropolyether alcohol, and 7 parts by mass of 5-amino-1-pentanol were dissolved in 100 parts by mass of dimethyl sulfoxide, respectively. The three were then mixed, and 0.01 parts by mass of tetrabutylammonium chloride was added. The mixture was stirred for reaction at room temperature for 1.5 hours, and then the temperature was raised to 54°C and the reaction was continued for 1.5 hours. After the solution was cooled to room temperature, the gum was precipitated with anhydrous ethanol, washed 3 times, and dried to obtain modified SBR; Tg was -36.32°C.

[0057] The preparation method of modified silica gel is as follows: 10 parts by mass of methyl vinyl silicone rubber is dissolved in 100 parts by mass of THF, and the methyl vinyl silicone rubber is stirred until it is completely dissolved, and then 1 part by mass of a mercapto modifier is added, wherein the mercapto modifier is obtained by mercaptopropionaldehyde, ethyl mercaptoacetate, and 1,3-dimercaptopropane in a mass ratio of 2:0.5:1.5, and the stirring is continued for 25 minutes, and 0.25 parts by mass of an initiator benzil dimethyl ether is added, and then a 365 nm wavelength is used in a closed chamber to irradiate the silica gel. The mixture was irradiated with UV-LED point light source for 1 hour. After the reaction was completed, a mixed solution of ethanol and deionized water in a volume ratio of 1:1 was used to precipitate the glue, and then it was dissolved in tetrahydrofuran again and precipitated with a mixed solution of ethanol and deionized water. This process was repeated three times to remove free thiol small molecules and avoid the odor of thiol reagents. Finally, it was placed in a vacuum oven at 40°C and dried for 23 hours. Then, it was placed in 14 parts by mass of 2M potassium hydroxide solution, stirred for 1 hour, and filtered to obtain modified silica gel with a Tg of -82.88°C.

[0058] The preparation method of environmentally friendly modified recycled masterbatch is as follows:

[0059] B1. The collected waste rubber soles are free of non-rubber impurities, and then cut and crushed into rubber particles with an average particle size of 5 mm;

[0060] B2. Add rubber particles, octadecyl ammonium and aromatic oil in a mass ratio of 100:2:8 into a high-speed mixer and mix for 5 minutes, wherein the temperature of the high-speed mixer is set to 73°C. After discharging, cool at room temperature to obtain environmentally friendly recycled materials;

[0061] B3. Add 20 parts by mass of environmentally friendly recycled materials, 4 parts by mass of natural rubber, 5 parts by mass of zinc oxide, and 15 parts by mass of cold-resistant agent into a mixer and mix for 3 minutes. When the temperature rises to 100°C, discharge the material to a calender and pass it through three times at room temperature to produce a sheet of environmentally friendly modified recycled masterbatch with a thickness of 4 mm.

[0062] (Example 2)

[0063] The preparation method of the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material comprises the following preparation steps:

[0064] (1) Weigh and prepare the following raw material components in parts by weight: 13 parts by weight of modified SBR, 18 parts by weight of NR, 70 parts by weight of BR, 8 parts by weight of modified silica gel, 3 parts by weight of phenolic resin, 25 parts by weight of environmentally friendly modified recycled masterbatch, 45 parts by weight of white carbon black, 10 parts by weight of PEG4000, 1 part by weight of stearic acid, 4.5 parts by weight of antioxidant, 2.3 parts by weight of sulfur, and 2.3 parts by weight of accelerator;

[0065] (2) adding the modified SBR and modified silica gel weighed in step (1) to an internal mixer and premixing for 4 minutes; then adding 6 parts by mass of carbon disulfide and heating to 80°C, mixing for 20 minutes, then cooling to room temperature and adding NR, BR, and phenolic resin, and continuing to mix for 4 minutes, then heating to 60°C, adding environmentally friendly modified recycled masterbatch and white carbon black in sequence, and mixing for 15 minutes; then continuing to add PEG4000, stearic acid, and antioxidant to the internal mixer, mixing for 8 minutes and starting to discharge; then passing through a double-roll plasticizer for 4 times to produce a thin sheet, the roller temperature is controlled at 60°C, the roller distance is adjusted to 0, and the roller distance is adjusted to 0.5 mm when discharging the sheet, and cooling at room temperature for at least 24 hours;

[0066] (3) The thin slices obtained in step (2) and the sulfur and accelerator weighed in step (1) are introduced into an open mill for refining for 5 minutes, and after cooling at room temperature for at least 12 hours, the thin slices are injection molded to obtain an extreme cold resistant and environmentally friendly modified recycled rubber sole.

[0067] Wherein, the preparation steps of modified SBR are as follows:

[0068] A1. Under argon protection, 600 parts by mass of cyclohexane, 45 parts by mass of deoxygenated styrene, 40 parts by mass of 4-vinylbenzyl bromide and 15 parts by mass of butadiene monomer, 0.5 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 40 ° C and preheated for 20 min; 582 parts by mass of 1.6 mol / L n-butyl lithium solution was added dropwise at 2s / 2s, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking was completed to obtain a broken hard segment material;

[0069] A2. Under argon protection, 600 parts by mass of cyclohexane, 10 parts by mass of deoxygenated styrene, 20 parts by mass of 4-vinylbenzyl bromide and 70 parts by mass of butadiene monomer, 0.5 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 842 parts by mass of 1.6 mol / L n-butyl lithium solution were added at 2s / drop, and the reaction was broken to remove trace water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking of impurities was completed, and then the polymerization reaction was initiated at 40°C for 40 minutes to obtain a soft segment material, and then the hard segment material with impurities was added, and the reaction was continued for 20 minutes. After the reaction was completed, 450 parts by mass of SnCl4 was added to continue the reaction for 20 minutes, and 110 parts by mass of isopropanol were added to terminate the reaction, and after water vapor condensation, it was extruded on a 120°C open mill to remove water to obtain a pre-modified SBR; the mass ratio of the soft segment material to the hard segment material with impurities was 6:4;

[0070] A3. 13 parts by mass of pre-modified SBR and 100 parts by mass of cyclohexane were mixed and stirred at 50 r / min to mix evenly, followed by adding 20 parts by mass of formic acid and 2 parts by mass of tween80, and after mixing evenly, the temperature was raised to 40°C, and 12 parts by mass of hydrogen peroxide were added dropwise at 2s / drop. After the addition was completed, the reaction was carried out for 24 hours, and then sodium carbonate was added to adjust the pH to neutral, and the oil phase was washed twice with deionized water and condensed with ethanol, and then washed and dried to obtain epoxidized pre-modified SBR;

[0071] A4. 10 parts by mass of epoxidized pre-modified SBR, 78 parts by mass of perfluoropolyether alcohol, and 8 parts by mass of 5-amino-1-pentanol were dissolved in 100 parts by mass of dimethyl sulfoxide, respectively, and then the three were mixed, and 0.02 parts by mass of tetrabutylammonium chloride was added. After stirring and reacting at room temperature for 2 hours, the temperature was raised to 55°C and the reaction was continued for 2 hours. After the solution was cooled to room temperature, the gum was precipitated with anhydrous ethanol, washed 4 times, and dried to obtain modified SBR; Tg was -38.36°C.

[0072] The preparation method of modified silica gel is as follows: 10 parts by mass of methyl vinyl silicone rubber is dissolved in 100 parts by mass of THF, and the methyl vinyl silicone rubber is stirred until it is completely dissolved, and then 3 parts by mass of a mercapto modifier is added, wherein the mercapto modifier is obtained by mercaptopropionaldehyde, ethyl mercaptoacetate, and 1,3-dimercaptopropane in a mass ratio of 2:1:2, and the stirring is continued for 30 minutes, and 0.26 parts by mass of an initiator benzil dimethyl ether is added, and then a UV-L with a wavelength of 365 nm is used in a closed chamber. Irradiate with ED point light source for 1.5 hours. After the reaction is completed, use a mixed solution of ethanol and deionized water in a volume ratio of 1:1 to precipitate the glue, and then dissolve it in tetrahydrofuran again and use a mixed solution of ethanol and deionized water to precipitate the glue. Repeat three times to remove free thiol small molecules and avoid the odor of thiol reagents. Finally, place it in a vacuum oven at 45°C to dry for 24 hours, put it into 16 parts by mass of 2M potassium hydroxide solution, stir it for 1.5 hours and filter it to obtain modified silica gel with a Tg of -86.64°C.

[0073] The preparation method of environmentally friendly modified recycled masterbatch is as follows:

[0074] B1. The collected waste rubber soles are removed of non-rubber impurities, and then cut and crushed into rubber particles with an average particle size of 10 mm;

[0075] B2. Add rubber particles, octadecyl ammonium and aromatic oil in a mass ratio of 100:4:10 into a high-speed mixer and mix for 6 minutes, wherein the temperature of the high-speed mixer is set to 75°C, and cool at room temperature after discharge to obtain environmentally friendly recycled materials;

[0076] B3. Add 25 parts by mass of environmentally friendly recycled materials, 5 parts by mass of natural rubber, 6 parts by mass of zinc oxide, and 18 parts by mass of cold-resistant agent into a mixer and mix for 4 minutes. When the temperature rises to 100°C, discharge the material to a calender and thinly pass it three times at room temperature to produce a sheet of environmentally friendly modified recycled masterbatch with a thickness of 5 mm.

[0077] (Example 3)

[0078] The preparation method of the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material comprises the following preparation steps:

[0079] (1) Weigh and prepare the following raw material components in parts by weight: 15 parts by weight of modified SBR, 20 parts by weight of NR, 75 parts by weight of BR, 10 parts by weight of modified silica gel, 4 parts by weight of phenolic resin, 30 parts by weight of environmentally friendly modified recycled masterbatch, 50 parts by weight of white carbon black, 12 parts by weight of PEG4000, 1.2 parts by weight of stearic acid, 5 parts by weight of antioxidant, 3.5 parts by weight of sulfur, and 3.5 parts by weight of accelerator;

[0080] (2) adding the modified SBR and modified silica gel weighed in step (1) to an internal mixer and premixing for 5 minutes; then adding 8 parts by mass of carbon disulfide and heating to 85°C, mixing for 25 minutes, then cooling to room temperature and adding NR, BR, and phenolic resin, and continuing to mix for 5 minutes, then heating to 65°C, adding environmentally friendly modified recycled masterbatch and white carbon black in sequence, and mixing for 17 minutes; then continuing to add PEG4000, stearic acid, and antioxidant to the internal mixer, mixing for 10 minutes and starting to discharge; then passing through a double-roll plasticizer for 4 times to produce a thin sheet, the roller temperature is controlled at 60°C, the roller distance is adjusted to 0, and the roller distance is adjusted to 0.5 mm when discharging the sheet, and cooling at room temperature for at least 24 hours;

[0081] (3) The thin slices obtained in step (2) and the sulfur and accelerator weighed in step (1) are introduced into an open mill for 6 minutes to produce sheets, and after cooling at room temperature for at least 12 hours, injection molding is performed to obtain an extreme cold resistant and environmentally friendly modified recycled rubber sole.

[0082] Wherein, the preparation steps of modified SBR are as follows:

[0083] A1. Under argon protection, 600 parts by mass of cyclohexane, 46 parts by mass of deoxygenated styrene, 39 parts by mass of 4-vinylbenzyl bromide and 15 parts by mass of butadiene monomer, 0.6 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 41 ° C and preheated for 20 min; 584 parts by mass of 1.6 mol / L n-butyl lithium solution was added dropwise at 3s / 3s, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking was completed to obtain a broken hard segment material;

[0084] A2. Under argon protection, 600 parts by mass of cyclohexane, 11 parts by mass of deoxygenated styrene, 19 parts by mass of 4-vinylbenzyl bromide, 70 parts by mass of butadiene monomer, and 0.6 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 41°C for preheating for 20 minutes; 844 parts by mass of 1.6 mol / L n-butyl lithium solution were added at 3s / drop, and the reaction was broken to remove trace water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking of impurities was completed, and then the polymerization reaction was initiated at 41°C for 41 minutes to obtain a soft segment material, and then the hard segment material with impurities broken was added, and the reaction was continued for 21 minutes. After the reaction was completed, 500 parts by mass of SnCl4 was added to continue the reaction for 20 minutes, and 112 parts by mass of isopropanol were added to terminate the reaction, and after water vapor condensation, it was extruded on a 120°C open mill to remove water to obtain a pre-modified SBR; the mass ratio of the soft segment material to the hard segment material with impurities broken was 7:3;

[0085] A3. 15 parts by mass of pre-modified SBR and 100 parts by mass of cyclohexane were mixed and stirred at 55 r / min to mix evenly, followed by adding 21 parts by mass of formic acid and 2.5 parts by mass of tween80, mixing evenly, heating to 41°C, adding 13 parts by mass of hydrogen peroxide at 3s / drop, reacting for 25h after the addition, then adding sodium carbonate to adjust the pH to neutral, washing twice with deionized water, taking the oil phase and condensing it with ethanol, and then washing and drying to obtain epoxidized pre-modified SBR;

[0086] A4. 11 parts by mass of epoxidized pre-modified SBR, 80 parts by mass of perfluoropolyether alcohol, and 9 parts by mass of 5-amino-1-pentanol were dissolved in 100 parts by mass of dimethyl sulfoxide, respectively, and then the three were mixed, and 0.03 parts by mass of tetrabutylammonium chloride was added. After stirring and reacting at room temperature for 2.5 hours, the temperature was raised to 56°C and the reaction was continued for 2.5 hours. After the solution was cooled to room temperature, the gum was precipitated with anhydrous ethanol, washed 5 times, and dried to obtain modified SBR; Tg was -36.94°C.

[0087] The preparation method of modified silica gel is as follows: 10 parts by mass of methyl vinyl silicone rubber is dissolved in 100 parts by mass of THF, and the methyl vinyl silicone rubber is stirred until it is completely dissolved, and then 5 parts by mass of a mercapto modifier is added, wherein the mercapto modifier is obtained by mercaptopropionaldehyde, ethyl mercaptoacetate, and 1,3-dimercaptopropane in a mass ratio of 2:1.5:2.5, and the stirring is continued for 35 minutes, and 0.27 parts by mass of an initiator benzil dimethyl ether is added, and then a 365 nm wavelength is used in a closed chamber. The mixture was irradiated with UV-LED point light source for 2 hours. After the reaction was completed, a mixed solution of ethanol and deionized water in a volume ratio of 1:1 was used to precipitate the glue, and then it was dissolved in tetrahydrofuran again and precipitated with a mixed solution of ethanol and deionized water. This process was repeated three times to remove free thiol small molecules and avoid the odor of thiol reagents. Finally, it was placed in a vacuum oven at 50°C and dried for 25 hours. Then, it was placed in 19 parts by mass of 2M potassium hydroxide solution, stirred for 2 hours and filtered to obtain modified silica gel with a Tg of -85.56°C.

[0088] The preparation method of environmentally friendly modified recycled masterbatch is as follows:

[0089] B1. Remove non-rubber impurities from the collected waste rubber soles, and then cut and crush them into rubber particles with a particle size of 15 mm;

[0090] B2. Add rubber particles, octadecyl ammonium and aromatic oil in a mass ratio of 100:5:13 into a high-speed mixer and mix for 7 minutes, wherein the temperature of the high-speed mixer is set to 77°C, and cool at room temperature after discharge to obtain environmentally friendly recycled materials;

[0091] B3. Add 30 parts by mass of environmentally friendly recycled materials, 6 parts by mass of natural rubber, 8 parts by mass of zinc oxide, and 20 parts by mass of cold-resistant agent into a mixing chamber and mix for 5 minutes. When the temperature rises to 100°C, discharge the material to a calender and pass it through three times at room temperature to produce a sheet of environmentally friendly modified recycled masterbatch with a thickness of 6 mm.

[0092] (Comparative Example 1)

[0093] The difference between Comparative Example 1 and Example 2 is only the preparation step of the modified SBR; the preparation step of the modified SBR of Comparative Example 1 is as follows: A1. Under argon protection, 600 parts by mass of cyclohexane, 85 parts by mass of deoxygenated styrene and 15 parts by mass of butadiene monomer, and 0.5 parts by mass of ditetrahydrofurfuryl propane are mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 582 parts by mass of 1.6 mol / L n-butyl lithium solution are added dropwise at 2s / drop, and the reaction is subjected to impurity breaking treatment to remove trace amounts of water and oxygen in the solution. When the color of the solution changes from transparent to light yellow, the impurity breaking is completed to obtain a hard segment material with impurities broken;

[0094] A2. Under argon protection, 600 parts by mass of cyclohexane, 30 parts by mass of deoxygenated styrene and 70 parts by mass of butadiene monomer, and 0.5 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 842 parts by mass of 1.6 mol / L n-butyl lithium solution were added at 2s / drop, and the reaction was broken to remove trace water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking of impurities was completed, and then the polymerization reaction was initiated at 40°C for 40 minutes to obtain a soft segment material, and then the hard segment material with impurities was added, and the reaction was continued for 20 minutes. After the reaction was completed, 450 parts by mass of SnCl4 was added to continue the reaction for 20 minutes, and 110 parts by mass of isopropanol were added to terminate the reaction, and after water vapor condensation, it was extruded on a 120°C open mill to remove water to obtain a pre-modified SBR; the mass ratio of the soft segment material to the hard segment material with impurities was 6:4;

[0095] A3. 13 parts by mass of pre-modified SBR and 100 parts by mass of cyclohexane were mixed and stirred at 50 r / min to mix evenly, followed by adding 20 parts by mass of formic acid and 2 parts by mass of tween80, and after mixing evenly, the temperature was raised to 40°C, and 12 parts by mass of hydrogen peroxide were added dropwise at 2s / drop. After the addition was completed, the reaction was carried out for 24 hours, and then sodium carbonate was added to adjust the pH to neutral, and the oil phase was washed twice with deionized water and condensed with ethanol, and then washed and dried to obtain epoxidized pre-modified SBR;

[0096] A4. 10 parts by mass of epoxidized pre-modified SBR, 78 parts by mass of perfluoropolyether alcohol, and 8 parts by mass of 5-amino-1-pentanol were dissolved in 100 parts by mass of dimethyl sulfoxide, respectively, and then the three were mixed, and 0.02 parts by mass of tetrabutylammonium chloride was added. After stirring and reacting at room temperature for 2 hours, the temperature was raised to 55°C and the reaction was continued for 2 hours. After the solution was cooled to room temperature, the gum was precipitated with anhydrous ethanol, washed 4 times, and dried to obtain modified SBR; Tg was -32.32°C.

[0097] (Comparative Example 2)

[0098] The difference between Comparative Example 2 and Example 2 is only the preparation step of the modified SBR; the preparation step of the modified SBR of Comparative Example 2 is as follows: A1. Under argon protection, 600 parts by mass of cyclohexane, 45 parts by mass of deoxygenated styrene, 40 parts by mass of 4-vinylbenzyl bromide and 15 parts by mass of butadiene monomer, 0.5 parts by mass of ditetrahydrofurfuryl propane are mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 582 parts by mass of 1.6 mol / L n-butyl lithium solution are added dropwise at 2s / drop, and the reaction is subjected to impurity breaking treatment to remove trace amounts of water and oxygen in the solution. When the color of the solution changes from transparent to light yellow, the impurity breaking is completed to obtain a hard segment material with impurities broken;

[0099] A2. Under argon protection, 600 parts by mass of cyclohexane, 10 parts by mass of deoxygenated styrene, 20 parts by mass of 4-vinylbenzyl bromide and 70 parts by mass of butadiene monomer, 0.5 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 842 parts by mass of 1.6 mol / L n-butyl lithium solution were added at 2s / drop, and the reaction was broken to remove trace water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking of impurities was completed, and then the polymerization reaction was initiated at 40°C for 40 minutes to obtain a soft segment material, and then the hard segment material with impurities was added, and the reaction was continued for 20 minutes. After the reaction was completed, 450 parts by mass of SnCl4 was added to continue the reaction for 20 minutes, and 110 parts by mass of isopropanol were added to terminate the reaction, and after water vapor condensation, it was extruded on a 120°C open mill to remove water to obtain a pre-modified SBR; the mass ratio of the soft segment material to the hard segment material with impurities was 6:4;

[0100] A3. 13 parts by mass of pre-modified SBR and 100 parts by mass of cyclohexane were mixed and stirred at 50 r / min to mix evenly, followed by adding 20 parts by mass of formic acid and 2 parts by mass of tween80, and after mixing evenly, the temperature was raised to 40°C, and 12 parts by mass of hydrogen peroxide were added dropwise at 2s / drop. After the addition was completed, the reaction was carried out for 24 hours, and then sodium carbonate was added to adjust the pH to neutral, and the oil phase was washed twice with deionized water and condensed with ethanol, and then washed and dried to obtain epoxidized pre-modified SBR;

[0101] A4. Dissolve 10 parts by mass of epoxidized pre-modified SBR and 78 parts by mass of perfluoropolyether alcohol in 100 parts by mass of dimethyl sulfoxide respectively, then mix the two, add 0.02 parts by mass of tetrabutylammonium chloride, stir and react at room temperature for 2 hours, then heat to 55°C and continue to react for 2 hours. After the solution is cooled to room temperature, precipitate the glue with anhydrous ethanol, wash 4 times, and dry to obtain modified SBR; Tg is -32.93°C.

[0102] (Comparative Example 3)

[0103] The difference between Comparative Example 3 and Example 2 is only the preparation step of the modified SBR; the preparation step of the modified SBR of Comparative Example 3 is as follows: A1. Under argon protection, 600 parts by mass of cyclohexane, 45 parts by mass of deoxygenated styrene, 40 parts by mass of 4-vinylbenzyl bromide and 15 parts by mass of butadiene monomer, 0.5 parts by mass of ditetrahydrofurfuryl propane are mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 582 parts by mass of 1.6 mol / L n-butyl lithium solution are added dropwise at 2s / drop, and the reaction is subjected to impurity breaking treatment to remove trace amounts of water and oxygen in the solution. When the color of the solution changes from transparent to light yellow, the impurity breaking is completed to obtain a hard segment material with impurities broken;

[0104] A2. Under argon protection, 600 parts by mass of cyclohexane, 10 parts by mass of deoxygenated styrene, 20 parts by mass of 4-vinylbenzyl bromide and 70 parts by mass of butadiene monomer, 0.5 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 842 parts by mass of 1.6 mol / L n-butyl lithium solution were added at 2s / drop, and the reaction was broken to remove trace water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking of impurities was completed, and then the polymerization reaction was initiated at 40°C for 40 minutes to obtain a soft segment material, and then the hard segment material with impurities was added, and the reaction was continued for 20 minutes. After the reaction was completed, 450 parts by mass of SnCl4 was added to continue the reaction for 20 minutes, and 110 parts by mass of isopropanol were added to terminate the reaction, and after water vapor condensation, it was extruded on a 120°C open mill to remove water to obtain a pre-modified SBR; the mass ratio of the soft segment material to the hard segment material with impurities was 6:4;

[0105] A3. 13 parts by mass of pre-modified SBR and 100 parts by mass of cyclohexane were mixed and stirred at 50 r / min to mix evenly, followed by adding 20 parts by mass of formic acid and 2 parts by mass of tween80, and after mixing evenly, the temperature was raised to 40°C, and 12 parts by mass of hydrogen peroxide were added dropwise at 2s / drop. After the addition was completed, the reaction was carried out for 24 hours, and then sodium carbonate was added to adjust the pH to neutral, and the oil phase was washed twice with deionized water and condensed with ethanol, and then washed and dried to obtain epoxidized pre-modified SBR;

[0106] A4. 10 parts by mass of epoxidized pre-modified SBR and 8 parts by mass of 5-amino-1-pentanol were dissolved in 100 parts by mass of dimethyl sulfoxide respectively, and then the two were mixed, and 0.02 parts by mass of tetrabutylammonium chloride was added. After stirring and reacting at room temperature for 2 hours, the temperature was raised to 55°C and the reaction was continued for 2 hours. After the solution was cooled to room temperature, the gum was precipitated with anhydrous ethanol, washed 4 times, and dried to obtain modified SBR; Tg was -18.29°C.

[0107] (Comparative Example 4)

[0108] The difference between Comparative Example 4 and Example 2 is only the preparation step of the modified SBR; the preparation step of the modified SBR in Comparative Example 4 is as follows: A1. Under argon protection, 600 parts by mass of cyclohexane, 45 parts by mass of deoxygenated styrene, 40 parts by mass of 4-vinylbenzyl bromide and 15 parts by mass of butadiene monomer, and 0.5 parts by mass of ditetrahydrofurfuryl propane are mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 582 parts by mass of 1.6 mol / L n-butyl lithium solution are added dropwise at 2s / drop, and the reaction is subjected to impurity breaking treatment to remove trace amounts of water and oxygen in the solution. When the color of the solution changes from transparent to light yellow, the impurity breaking is completed to obtain a hard segment material with impurities broken;

[0109] A2. Under argon protection, 600 parts by mass of cyclohexane, 10 parts by mass of deoxygenated styrene, 20 parts by mass of 4-vinylbenzyl bromide and 70 parts by mass of butadiene monomer, 0.5 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 40°C for 20 minutes; 842 parts by mass of 1.6 mol / L n-butyl lithium solution were added dropwise at 2s / drop, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, After the impurities are broken, the polymerization reaction is initiated at 40°C for 40 minutes to obtain a soft segment, and then the hard segment with impurities broken is added and the reaction is continued for 20 minutes. After the reaction is completed, 450 parts by weight of SnCl4 is added to continue the reaction for 20 minutes, and 110 parts by weight of isopropanol are added to terminate the reaction. After water vapor condensation, the modified SBR is obtained by extrusion on an open mill at 120°C to remove water. The mass ratio of the soft segment to the hard segment with impurities broken is 6:4; Tg is -12.34°C.

[0110] (Comparative Example 5)

[0111] The difference between Comparative Example 5 and Example 2 is that the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material adopts SBR; the preparation steps of SBR in Comparative Example 5 are as follows: A1. Under argon protection, 600 parts by mass of cyclohexane, 85 parts by mass of deoxygenated styrene and 15 parts by mass of butadiene monomer, and 0.5 parts by mass of ditetrahydrofurfurylpropane are mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 582 parts by mass of 1.6 mol / L n-butyl lithium solution are added dropwise at 2s / drop, and the reaction is subjected to impurity breaking treatment to remove trace amounts of water and oxygen in the solution. When the color of the solution changes from transparent to light yellow, the impurity breaking is completed, and the impurity-breaking hard segment material is obtained;

[0112] A2. Under argon protection, 600 parts by mass of cyclohexane, 30 parts by mass of deoxygenated styrene and 70 parts by mass of butadiene monomer, and 0.5 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 40°C for preheating for 20 minutes; 842 parts by mass of 1.6 mol / L n-butyl lithium solution were added dropwise at 2s / drop, and the reaction was broken to remove trace water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking of impurities was completed, and then the polymerization reaction was initiated at 40°C for 40 minutes to obtain a soft segment material, and then the broken hard segment material was added, and the reaction was continued for 20 minutes. After the reaction was completed, 450 parts by mass of SnCl4 was added to continue the reaction for 20 minutes, and 110 parts by mass of isopropanol was added to terminate the reaction, and after water vapor condensation, it was extruded on a 120°C open mill to remove water to obtain SBR; the mass ratio of the soft segment material to the broken hard segment material was 6:4; Tg was -9.2°C.

[0113] (Comparative Example 6)

[0114] The only difference between Comparative Example 6 and Example 2 is that the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material adopts methyl vinyl silicone rubber, and the Tg of methyl vinyl silicone rubber is -58.8°C.

[0115] (Comparative Example 7)

[0116] The difference between Comparative Example 7 and Example 2 is only step (2); step (2) of Comparative Example 7 is as follows: the modified SBR, modified silica gel, NR, BR, and phenolic resin weighed in step (1) are kneaded for 4 minutes, then the temperature is raised to 60°C, and the environmentally friendly modified recycled masterbatch and white carbon black are added in sequence, and kneaded for 15 minutes; then PEG4000, stearic acid, and antioxidant are added to the internal mixer, and the material is discharged after kneading for 8 minutes; then the thin sheet is passed through a double-roll plasticizer for 4 times, the roller temperature is controlled at 60°C, the roller distance is adjusted to 0, and the roller distance is adjusted to 0.5 mm when discharging the sheet, and the sheet is cooled at room temperature for at least 24 hours.

[0117] Effect example:

[0118] Self-repairing performance test: The extreme cold resistant and environmentally friendly modified recycled rubber sole composite materials obtained in the embodiment and the comparative example were cut and then connected together, and then heat treated at 80° C. for 2 h to observe whether the two sections were reconnected.

[0119] Table 1 below shows the performance test results of the extreme cold resistant and environmentally friendly modified recycled rubber sole composite materials obtained in the examples and comparative examples:

[0120] Table 1

[0121]

[0122] It can be seen from Table 1 that compared with the extreme cold resistant environmentally friendly modified recycled rubber sole composite materials prepared in the embodiment and the comparative example, the extreme cold resistant environmentally friendly modified recycled rubber sole composite materials prepared in the embodiment have better cold resistance, low temperature folding resistance, tensile strength and self-repairing performance.

[0123] Compared with Example 2, the modified SBR in Comparative Example 1 is obtained by copolymerizing styrene and butadiene, and then epoxidizing and grafting perfluoropolyether alcohol and 5-amino-1-pentanol. The cold resistance, low-temperature folding resistance and tensile strength of the extreme cold-resistant and environmentally friendly modified recycled rubber sole composite material obtained in Comparative Example 1 are weaker than those in Example 2. This is because in the subsequent preparation of the extreme cold-resistant and environmentally friendly modified recycled rubber sole composite material, no benzyl trithiocarbonate derivative is formed, and the environmentally friendly modified recycled masterbatch is not subjected to secondary regeneration and degradation.

[0124] Compared with Example 2, the modified SBR in Comparative Example 2 is obtained by copolymerizing styrene, butadiene, and 4-vinylbenzyl bromide and then epoxidizing and grafting perfluoropolyether alcohol. The extreme cold-resistant and environmentally friendly modified recycled rubber sole composite material obtained in Comparative Example 2 has weaker cold resistance, low-temperature folding resistance, and tensile strength than that in Example 2, and has no self-repairing performance.

[0125] Compared with Example 2, the modified SBR in Comparative Example 3 is obtained by copolymerizing styrene, butadiene, and 4-vinylbenzyl bromide, and then epoxidizing and grafting 5-amino-1-pentanol; the cold resistance, low-temperature folding resistance, and tensile strength of the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material obtained in Comparative Example 3 are weaker than those in Example 2.

[0126] Compared with Example 2, the modified SBR in Comparative Example 4 is obtained by copolymerizing styrene, butadiene, and 4-vinylbenzyl bromide. The extreme cold-resistant and environmentally friendly modified recycled rubber sole composite material obtained in Comparative Example 4 has weaker cold resistance, low-temperature folding resistance, and tensile strength than those in Example 2, and has no self-repairing performance.

[0127] Compared with Example 2, the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material in Comparative Example 5 adopts SBR copolymerized with styrene and butadiene; the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material prepared in Comparative Example 3 is weaker in cold resistance, low temperature folding resistance and tensile strength than that in Example 2, and has no self-repairing performance.

[0128] Compared with Example 2, the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material of Comparative Example 6 adopts methyl vinyl silicone rubber. Compared with Example 2, the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material prepared in Comparative Example 3 has weaker cold resistance, low temperature folding resistance and tensile strength, and has no self-repairing performance.

[0129] Compared with Example 2, Example 7 uses the traditional mixing process to mix the raw material components of the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material. The tensile strength of the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material obtained in Example 3 is weaker than that in Example 2.

[0130] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Extreme cold resistant and environmentally friendly modified recycled rubber sole composite material, characterized in that: In terms of weight, the raw material components include 10 to 15 parts by weight of modified SBR, 15 to 20 parts by weight of NR, 65 to 75 parts by weight of BR, 5 to 10 parts by weight of modified silica gel, 2 to 4 parts by weight of phenolic resin, 20 to 30 parts by weight of environmentally friendly modified recycled masterbatch, 40 to 50 parts by weight of white carbon black, 8 to 12 parts by weight of PEG4000, 0.8 to 1.2 parts by weight of stearic acid, 4 to 5 parts by weight of antioxidant, 1 to 3.5 parts by weight of sulfur, and 1 to 3.5 parts by weight of accelerator.

2. The extreme cold resistant and environmentally friendly modified recycled rubber sole composite material according to claim 1, characterized in that: The modified SBR is obtained by copolymerizing styrene, butadiene and 4-vinylbenzyl bromide, and then epoxidizing and grafting perfluoropolyether alcohol and 5-amino-1-pentanol.

3. The extreme cold resistant and environmentally friendly modified recycled rubber sole composite material according to claim 1, characterized in that: The modified silica gel is obtained by modifying methyl vinyl silicone rubber with mercaptopropionaldehyde, ethyl mercaptoacetate and 1,3-dimercaptopropane.

4. The extreme cold resistant and environmentally friendly modified recycled rubber sole composite material according to claim 1, characterized in that: The environmentally friendly modified recycled masterbatch is obtained by crushing and cutting waste rubber soles from which non-rubber impurities are removed into rubber particles, kneading the rubber particles with octadecyl ammonium and aromatic oil, and then mixing with natural rubber, zinc oxide and a cold-resistant agent to obtain the masterbatch.

5. A method for preparing an extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material, characterized in that: The method comprises the following preparation steps: (1) Weighing and preparing the raw material components by weight of the extreme cold resistant and environmentally friendly modified recycled rubber sole composite material according to any one of claims 1 to 4; (2) adding the modified SBR and modified silica gel weighed in step (1) to an internal mixer and premixing for 3 to 5 minutes; then adding 4 to 8 parts by weight of carbon disulfide and heating to 75 to 85° C., mixing for 15 to 25 minutes, then cooling to room temperature and adding NR, BR, and phenolic resin, and continuing to mix for 3 to 5 minutes, then heating to 55 to 65° C., adding environmentally friendly modified recycled masterbatch and white carbon black in sequence, and mixing for 13 to 17 minutes; then continuing to add PEG4000, stearic acid, and antioxidant to the internal mixer, mixing for 6 to 10 minutes, and then starting to discharge; then passing through a double-roll plasticizer for 4 times to produce a thin sheet, the roller temperature is controlled at 60° C., the roller gap is adjusted to 0, and the roller gap is adjusted to 0.5 mm when the sheet is discharged, and the sheet is cooled at room temperature and placed for at least 24 hours; (3) The thin slices obtained in step (2) and the sulfur and accelerator weighed in step (1) are introduced into an open mill for refining for 3 to 6 minutes to produce sheets, and after cooling at room temperature for at least 12 hours, injection molding is performed to obtain an extreme cold resistant and environmentally friendly modified recycled rubber sole.

6. The method for preparing the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material according to claim 5, characterized in that: The preparation steps of the modified SBR are as follows: A1. Under argon protection, 600 parts by mass of cyclohexane, 44 to 46 parts by mass of deoxygenated styrene, 39 to 41 parts by mass of 4-vinylbenzyl bromide and 15 parts by mass of butadiene monomer, 0.4 to 0.6 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 39 to 41 ° C and preheated for 20 min; 580 to 584 parts by mass of 1.6 mol / L n-butyl lithium solution was added dropwise at 1 to 3s / drop, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light yellow, the breaking was completed to obtain a broken hard segment material; A2. Under argon protection, 600 parts by mass of cyclohexane, 9 to 11 parts by mass of styrene treated by deoxygenation, 19 to 21 parts by mass of 4-vinylbenzyl bromide and 70 parts by mass of butadiene monomer, 0.4 to 0.6 parts by mass of ditetrahydrofurfuryl propane were mixed and placed in a constant temperature water bath at 39 to 41 ° C for 20 minutes; 840 to 844 parts by mass of 1.6 mol / L n-butyl lithium solution was added dropwise at 1 to 3s / drop, and the reaction was broken to remove trace amounts of water and oxygen in the solution. When the color of the solution changed from transparent to light When it turns yellow, the impurities are broken, and then the polymerization reaction is initiated at 39-41°C for 39-41 minutes to obtain a soft segment, and then the impurities-broken hard segment is added, and the reaction is continued for 19-21 minutes. After the reaction is completed, 400-500 parts by weight of SnCl4 are added to continue the reaction for 19-20 minutes, and 108-112 parts by weight of isopropanol are added to terminate the reaction, and after water vapor condensation, it is extruded on a 120°C open mill to remove water to obtain a pre-modified SBR; the mass ratio of the soft segment to the impurities-broken hard segment is 5-7:3-5; A3. 10 to 15 parts by mass of pre-modified SBR and 100 parts by mass of cyclohexane were mixed and stirred at 45 to 55 r / min to mix evenly, and then 19 to 21 parts by mass of formic acid and 1.5 to 2.5 parts by mass of tween80 were added. After mixing evenly, the temperature was raised to 39 to 41°C, and 11 to 13 parts by mass of hydrogen peroxide were added dropwise at a rate of 1 to 3 seconds per drop. After the addition was completed, the reaction was continued for 23 to 25 hours, and then sodium carbonate was added to adjust the pH to neutral, and the oil phase was washed twice with deionized water and condensed with ethanol, and then washed and dried to obtain epoxidized pre-modified SBR; A4. 9 to 11 parts by mass of epoxidized pre-modified SBR, 75 to 80 parts by mass of perfluoropolyether alcohol, and 7 to 9 parts by mass of 5-amino-1-pentanol are dissolved in 100 parts by mass of dimethyl sulfoxide, respectively, and then the three are mixed, and 0.01 to 0.03 parts by mass of tetrabutylammonium chloride are added. After stirring and reacting at room temperature for 1.5 to 2.5 hours, the temperature is raised to 54 to 56°C and the reaction is continued for 1.5 to 2.5 hours. After the solution is cooled to room temperature, the gum is precipitated with anhydrous ethanol, washed 3 to 5 times, and dried to obtain modified SBR.

7. The method for preparing the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material according to claim 5, characterized in that: The preparation method of the modified silica gel is as follows: 10 parts by mass of methyl vinyl silicone rubber is dissolved in 100 parts by mass of THF, and the methyl vinyl silicone rubber is stirred until the methyl vinyl silicone rubber is completely dissolved, and then 1 to 5 parts by mass of a mercapto modifier is added, wherein the mercapto modifier is obtained by mercaptopropionaldehyde, ethyl mercaptoacetate, and 1,3-dimercaptopropane in a mass ratio of 2:0.5 to 1.5:1.5 to 2.5, and the stirring is continued for 25 to 35 minutes, and 0.25 to 0.27 parts by mass of an initiator benzil dimethyl ether is added, and then the initiator is used in a closed chamber. Irradiate with a UV-LED point light source with a wavelength of 365nm for 1 to 2 hours. After the reaction is completed, use a mixed solution of ethanol and deionized water in a volume ratio of 1:1 to precipitate the glue, and then dissolve it in tetrahydrofuran again and precipitate the glue with a mixed solution of ethanol and deionized water. Repeat three times to remove free thiol small molecules and avoid the odor of thiol reagents. Finally, place it in a vacuum oven at 40 to 50°C and dry it for 23 to 25 hours. Then, put it into 14 to 19 parts by mass of 2M potassium hydroxide solution, stir it for 1 to 2 hours and filter it to obtain modified silica gel.

8. The method for preparing the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material according to claim 5, characterized in that: The preparation method of the environmentally friendly modified recycled masterbatch is as follows: B1. Remove non-rubber impurities from the collected waste rubber soles, and then cut and crush them into rubber particles with a particle size of 5 to 15 mm; B2. Add rubber particles, octadecyl ammonium and aromatic oil in a mass ratio of 100:2-5:8-13 into a high-speed mixer and mix for 5-7 minutes, wherein the temperature of the high-speed mixer is set at 73-77°C, and cool at room temperature after discharge to obtain environmentally friendly recycled materials; B3. Add 20-30 parts by mass of environmentally friendly recycled materials, 4-6 parts by mass of natural rubber, 5-8 parts by mass of zinc oxide, and 15-20 parts by mass of cold-resistant agent into a mixer and mix for 3-5 minutes. When the temperature rises to 100°C, discharge the material to a calender and thin it three times at room temperature to produce a sheet of environmentally friendly modified recycled masterbatch with a thickness of 4-6 mm.

9. The method for preparing the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material according to claim 8, characterized in that: The cold-resistant agent is prepared by compounding dioctyl sebacate and dioctyl phthalate in a mass ratio of 1:1.2-3.

5.

10. The method for preparing the extremely cold-resistant and environmentally friendly modified recycled rubber sole composite material according to claim 5, characterized in that: The accelerator is prepared by mixing 2,2'-dibenzothiazole disulfide, tetramethylthiuram monosulfide, N-tert-butyl-2-benzothiazole sulfonamide and diphenylguanidine in a mass ratio of 12:1:2:2.